Correlation-Changed-EMD Algorithm for Single Frequency-Sweep Interferometry Signal of High-Speed Rotating Structure Clearance Measurement - Ren, Yilin; Zhang, Peng; Shao, Bin; Liu, Xianming; Lei, Xiaohua; Liu, Hao; Zou, Wenfei (IEEE sensors journal, 2023)
Frequency-sweep interferometry (FSI) technology enables high-speed axial clearance measurements but is subject to errors caused by the Doppler effect. Adding auxiliary paths to eliminate the Doppler effect may cause slower measurement speed and low accuracy. In this article, the characteristics of the axial clearance variations are analyzed. Subsequently, a correlation-changed empirical mode decomposition (Cor-CEMD) algorithm is developed. The optimal construction value is coarsely located by the correlation algorithm, minimizing the amount of computational data. Then, the optimal construction value is precisely located using changed empirical mode decomposition (EMD) algorithm, thus achieving fast and high-precision clearance reconstruction. This algorithm has a good suppression effect on changes of rotation speed and fluctuation of peak-to-peak clearance. Simulations and experiments have demonstrated that the algorithm has a good effect on high-speed axial clearance reconstruction. For a variable clearance of 4 kHz, the maximum reconstruction error is reduced by 98.4% using the Cor-CEMD algorithm compared with using the EMD algorithm, and the demodulation speed can reach 28 kHz.